Distal phalangeal bone erosions observed by HR-pQCT in patients with psoriatic onycholysis. (4th September 2020) - Villani, Axel P; Boutroy, Stéphanie; Coutisson, Céline; Carlier, Marie-Christine; Barets, Loïs; Marotte, Hubert; Richert, Bertrand; Chapurlat, Roland D; Jullien, Denis; Confavreux, Cyrille B
Abstract: Objectives: PsA prevalence among skin psoriasis is ∼30%. Nail psoriasis, especially onycholysis, is present in >70% of PsA and the risk of developing PsA is more than doubled in patients with nail involvement. We hypothesized that onycholysis may be associated with early bone erosions of the DIP joint without harbouring PsA symptoms. Methods: We compared tendon thickness, assessed by US, and bone erosions, assessed by high-resolution peripheral quantitative CT, of the DIP joint in patients with psoriatic onycholysis without PsA (ONY) with those in patients with cutaneous psoriasis only (PSO). We used patients with PsA as reference (PsA group), and healthy age-matched controls (CTRL). Differences between groups were assessed by analysis of variance tests followed by post hoc analysis using the Scheffe method. Results: Mean (s.e.m .) age of the 87 participants (61% males) was 45.2 (1.3) years. The mean extensor tendon thickness was significantly larger in ONY than in PSO patients. In the PsA group, 68% of patients exhibited erosions of three different shapes: V-, Omega- and U-shape. Association with erosions was greater in the ONY group than in the PSO group (frequency: 57 vs 14%; P < 0.001; mean number of erosions: 1.10 (0.35) vs 0.03 (0.03); P < 0.001). Conclusion: Onycholysis was associated with significant enthesopathy and bone erosions in our cohort. These data support the pathogenic role of enthesopathy in PsA. Onycholysis may be considered as a surrogate marker of severity in psoriasis. Trial registration: ClinicalTrails.gov, https://clinicaltrials.gov, NCT02813720